Patients’ perceptions of the frequency of medication counseling by pharmacists: A Qualitative Case Study - Dian Meiliani Yulis; Nun Sudiar Astati; Hairuddin K; Julia Fitrianingsih (LPPM Politeknik Sandi Karsa, South Sulawesi, Indonesia, 2026)
Introduction: Medication counseling is an essential component of patient-centered pharmaceutical care, contributing to medication safety, adherence, and patient satisfaction. In hospital pharmacy settings, counseling practices are often influenced by workload and service constraints, resulting in variability in counseling frequency. Understanding how patients perceive and interpret the frequency of medication counseling is therefore important for improving the quality of pharmacy services. This study aimed to explore patients’ perceptions of the frequency of medication counseling provided by pharmacists and to examine its role in shaping patient satisfaction within a hospital pharmacy setting. Research Methodology: A qualitative case study design was employed at the pharmacy installation of a regional general hospital in Indonesia. Data were collected through in-depth interviews with patients, pharmacists, and supporting staff, complemented by non-participant observations and document review. Participants were selected using purposive sampling. Data were analyzed thematically through data condensation, data display, and conclusion drawing, with credibility ensured through triangulation of sources and techniques. Results: The findings revealed that medication counseling frequency was delivered inconsistently and varied according to workload, patient volume, and medication characteristics. Patients perceived frequent counseling as a sign of professional care that enhanced understanding, confidence, and trust in pharmacists. Consistent counseling contributed positively to patient satisfaction, whereas limited counseling led to uncertainty in medication use. Organizational factors, such as staffing limitations and service flow, were identified as key constraints on counseling practices. Conclusion: Medication counseling frequency is a meaningful experiential factor that shapes patient satisfaction and the quality of pharmacist-patient interactions. Strengthening counseling consistency through organizational support and standardized practices may improve patient-centered pharmaceutical care in hospital settings.